Green Marketing Strategies and Consumer Purchasing Behavior: Moderating Role of Environmental Awareness Among Supermarket Consumers in Lagos State - Haveez Omotayo Ahmadu; Abdulazeez Alhaji Salau; Dolapo Stephen Akinwumi; Oluseyi Ajayi; Femi Seun Benjamin; Kayode Muhammed Ibrahim (Journal of Consumer Sciences, 2026)
Background:  The Nigerian retail industry has grown substantially in the last ten years, especially in Lagos. There is a growing concern about environmental issues but little research on green marketing strategies and consumer purchasing behavior in Lagos supermarkets with particular reference to environmental awareness have been conducted. Purpose: This research aims to analyze green marketing strategies (eco-labeling, green packaging, and environmental advertising) affect consumer purchases behavior among supermarket consumers in Lagos State, Nigeria, with environmental awareness as a moderating variable. Method: The design used was a quantitative explanatory survey. The population comprise of 950 adult consumers of supermarkets (18 years and above) residing in Lagos State. A sample size of 281 was computed using the Taro Yamane formula. Purposive sampling was utilized, equally 280 valid response was actualized out of the distributed questionnaire. Hypothesis testing was analyzed through Partial Least Squares Structural Equation Modeling using Smart-PLS 4.0. Findings: The three green marketing strategies positively impact consumer behavior, with eco-labeling the strongest. Environmental awareness influenced eco-labeling and consumer behavior and environmental advertising and consumer behavior. However, it had no effect on green packaging and consumer behavior. Conclusion:  The study concluded that eco-labeling is the most suitable green marketing strategy in supermarkets in Lagos for environmentally conscious consumers. Supermarket operators should offer environmental awareness programs along with eco-labeling to promote sustainable consumer behavior. Research Implication: Supermarket managers should focus on investment into internationally recognized eco-certification systems and online environmental advertisement to environmentally conscious consumer groups.